Pericardial defect presenting as acute pericarditis. - Carty, J E (1975)
A case of herniation of the left atrial appendage, through a defect in the pericardium, is described in a 16-year-old boy who was below the third percentile for height and weight. The clinical presentation was an acute pericarditis. Widespread inversion of T waves on the electrocardiogram and collapse of the lower lobe of the left lung with pleural effusion developed. Thoracotomy showed strangulation of the atrial appendage which was excised, and the pericardial defect repaired. After operation there was a striking improvement in the electrocardiogram and a rapid gain in weight. Syndromes caused by pericardial defects are reviewed.